Shelf-life of chilled cut orange determined by sensory quality - Rocha, A. M. C. N. (2011)
The shelf-life of chilled cut orange was evaluated in terms of physical and chemical quality characteristics, microbial contamination and sensorial acceptability. After minimal processing (peeling and cutting), fresh orange was stored in air at 4 °C. Evaluations were performed at different times of storage. The respiration rate of the fresh-cut orange was also evaluated. No significant increase was noticed in relation to the whole fruit which means that this was not the factor responsible for an accelerated deterioration of the product. During the first eight days of storage the major quality parameters remain almost unchangeable, except for titratable acidity which decreased around 36% and ascorbic acid content which decreased around 22%. With respect to microbial contamination low temperature determined a considerable shelf-life (15 days). Sensory quality was the parameter which determined the shelf-life of cut orange to five days at 4 °C due to flavour changes.